PENDEKATAN SHOJINKA DALAM MEMINIMASI TOTAL WORK IN PROCESS PADA PRODUKSI SPRINGBED (Studi Kasus di PT. Malindo Intitama Raya) - Rendragraha, Derry; Tama, Ishardita Pambudi; Tantrika, Ceria Farela Mada (Jurnal Rekayasa dan Manajemen Sistem Industri, 2015)
Abstract Work In Process is a material that has entered the production process but not a finished product yet. The amount of WIP is included in the company’s losses can be caused by the load of each work station that is not balanced. PT Malindo Intitama Raya (MIR) is a company which engaged in the furniture manufacturing and trading. The problems experienced by the company was the number of work in process in 10 of 15 process. The company made a policy to keep producing at least 5 units springbed a day that will become a buffer stock in case of residual products. Problems of work in process is expected to be solved with the flexibility of workers. Flexibility worker in this case is to change the number of workers on a production line if production demands change. The method used in the flexibility of workers is use tools shojinka’s approach with gang process chart. There were five scenarios for the target product produced in this research, there are 5, 6, 7, 8 and 9 products. The result on reduction in the amount of 5 products work in process in the 4 process with total of 5 units and additional work in process in 2 process with 2 total units. Keyword : springbed, work in process, flexibility of workers, shojinka, gang process chart